2013
DOI: 10.1371/journal.pone.0067547
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Inhibitor Binding to Peptidyl-tRNA Hydrolase: Binding Studies and Structure Determination of Unbound and Bound Peptidyl-tRNA Hydrolase from Acinetobacter baumannii

Abstract: The incidences of infections caused by an aerobic Gram-negative bacterium, Acinetobacter baumannii are very common in hospital environments. It usually causes soft tissue infections including urinary tract infections and pneumonia. It is difficult to treat due to acquired resistance to available antibiotics is well known. In order to design specific inhibitors against one of the important enzymes, peptidyl-tRNA hydrolase from Acinetobacter baumannii, we have determined its three-dimensional structure. Peptidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…In the Ramachandran plot, 180 of the 182 residues are in the preferred regions, Glu38 and Ala44 are in the allowed region, and only Tyr55 is in the disallowed region. However, the torsion angles of the equivalent residues of Tyr55 are also in the disallowed regions in some other Pths . The conformation of Tyr55 therefore seems to be reasonable.…”
Section: Resultsmentioning
confidence: 92%
“…In the Ramachandran plot, 180 of the 182 residues are in the preferred regions, Glu38 and Ala44 are in the allowed region, and only Tyr55 is in the disallowed region. However, the torsion angles of the equivalent residues of Tyr55 are also in the disallowed regions in some other Pths . The conformation of Tyr55 therefore seems to be reasonable.…”
Section: Resultsmentioning
confidence: 92%
“…In contrast, the corresponding r.m.s. shifts among C α traces of Pth enzymes belonging to Gram‐negative bacteria [24–29] were found to be in the range of 0.7–1.4 Å. It showed that the path of the polypeptide chain of a Pth enzyme from a Gram‐positive bacterium differed slightly from those of Gram‐negative bacteria.…”
Section: Resultsmentioning
confidence: 97%
“…SpPth shows sequence identities ranging from 30% to 32% ( Fig. 1) with Pth enzymes of other bacteria whose structures are known [24][25][26][27][28][29][30][31]. The three-dimensional structure of SpPth has been determined at 2.19 Å resolution.…”
Section: Introductionmentioning
confidence: 99%
“…During crystallization trials with lower concentrations of Pth1 (10 or 20 mg ml À1 ), limited crystal formation was observed even after several weeks. At the high concentration (120 mg ml Schmitt et al, 1997), P. aeruginosa Pth1 (PDB entry 4fyj; Hughes et al, 2012), F. tularensis Pth1 (PDB entry 3nea; Clarke et al, 2011), M. smegmatis Pth1 (PDB entry 3p2j, Kumar et al, 2012) and Acinetobacter baumannii Pth1 (PDB entry 3wh4, Kaushik et al, 2013). The regions with high variations in tertiary structure between the enzymes are indicated with arrows.…”
Section: Resultsmentioning
confidence: 99%